Molecular dynamics investigation of the structural and energetic properties of CeO2-MO: X (M = Gd, La, Ce, Zr) nanoparticles - De Mendonca, Joao Paulo A.; Lourenco, Tuanan C.; Freitas, Luis Paulo M. [UNESP]; Santo, Anderson A. E. [UNESP]; Feliciano, Gustavo T. [UNESP]; Da Silva, Juarez L. F. (Royal Society of Chemistry (RSC), 2021)
CeO2-based materials have played a critical role in catalysis, where the substrate particles have reduced in size year by year due to experimental achievements in synthesis control. Thus, there is increasing interest to improve our atomistic understanding of the structural and energetic properties of mixed CeO2-based nanoparticles of 1 nm to 5 nm. Here, we employed classical molecular dynamics (MD) simulations to study the following solid solutions, CeO2-Gd2O3, CeO2-La2O3, CeO2-Ce2O3, and CeO2-ZrO2, using 5 compositions (0, 25, 50, 75, and 100%). The amorphization and re-cystallization process via MD simulations was employed to generate the nanoparticles, which were characterized by several analyses. We found that even in small CeO2 concentrations, the systems maintain the cubic fluorite structure and the truncated octahedron shape found in pure ceria, evidencing the strong influence of Ce4+ on the nanoparticle morphology due to the higher phase transition temperature of the CeO2 compound. On the other hand, the addition of the 3+ species leads to the spontaneous appearance of higher concentrations of solvated cations and vacancies near to the surface of the CeO2-based solutions. Beyond that, the 3+ species also influence the electrostatic potential in the nanoparticle surface, and hence controlling the 3+-4+ ratio may be an interesting approach to control the nanoparticle physicochemical properties for catalytic purposes. This journal is